Movements, recapture rate and length increment of tagged pikeperch (Sander lucioperca) – a basis for management in large lakes. (December 2015) - Andersson, M.; Degerman, E.; Persson, J.; Ragnarsson‐Stabo, H.
Abstract: Movements, site fidelity, exploitation rate and total length (TL) increment of pikeperch, Sander lucioperca L., were studied by tagging 3977 pikeperch, of 334 mm mean TL, in Lake Mälaren in 1994. Fish were recaptured in gillnets, trap nets and to a lesser extent with rod and line. Total recapture rate was 30.4%, with 50% of the recaptures made within 8.4 km of the release site. Movements were restricted during summer, whereas movements from shallow to deeper basins were frequent in autumn. The yearly TL increment was estimated at 99 mm for fish 300 mm long at release and 42 mm for fish of 400 mm at release. The results have direct implications for future management, as the mortality of undersized fish in the fishery; the strong site fidelity and fast growth indicate that fishery closures may be an effective measure to attain a larger stock of fish above the size limit.